"I Still Don't Know What Happened, Complete Blackout": a Content Analysis of Tweets Referencing Alcohol-Induced Amnesia. (27th May 2021) - Ward, Rose Marie; Riordan, Benjamin C.; Merrill, Jennifer E.
Abstract: Twitter provides a real-time venue for monitoring alcohol consumption and negative alcohol-related consequences. "Blackouts, " defined as events involving alcohol-induced amnesia, are commonly endorsed among social drinkers. However, the term "blackout" has been used in popular culture to describe being intoxicated. Objective: We qualitatively examined the content of alcohol-related blackouts posts ("Tweets") on Twitter, focusing on reflections post-drinking that involved clear references to memory loss. Methods: We examined publically available Tweets that referenced blackouts after an alcohol consumption event ( n  = 3, 574). Results: Twitter represents a relatively unfiltered glimpse at reflections on alcohol-induced amnesia. As hypothesized, most tweets referencing blackouts did not clearly describe amnesia. In the Tweets that clearly reference amnesia, we identified several themes. Tweeters referenced an 'AlterEgo' who was responsible for all the intoxicated behaviors that were inconsistent with the Tweeter's personality. Additionally, the Tweets discussed ways in which the drinker recovered memories (e.g. from friends, from social media), other events that occurred during the amnesia (e.g. loss of items, help from friends, sexual experiences), and regret about having lost memories. Some Tweeters requested assistance from their followers to reconstruct their drinking event. Tweets have the potential to set norms about acceptable behaviors or scripts following a blackout. Conclusions: Since most blackout Tweets are ambiguous with regards to alcohol-induced amnesia, these Tweets might be leading people to believe that blackouts are passing out or just periods of heavy intoxication. In addition, themes from these Tweets can inform future interventions by using the cognitions surrounding this high-risk behavior.